Analisis Pengaruh Kualitas dan Merek Terhadap Keputusan Pembelian Sepatu Merek Eiger di Makassar - Jihan; Andryanus Paridi; Johannes Baptista Halik (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
This research is a quantitative study which aims to determine the simultaneous and partial influence of the marketing mix consisting of product, quality and brand on purchasing decisions for Eiger shoe products in Makassar. This research uses primary data, and is obtained directly from questionnaires filled out by respondents. The population in this research is various groups of nature lovers in Makassar. The sample in this study amounted to 61 respondents who were determined using the purposive sampling method. The data analysis method used is the multiple linear regression analysis method. Based on the results of the analysis using PLS30, it is concluded that the influence of quality is significant with a value of 17.7%, the influence of brand is significant with a value of 73.7% on purchasing decisions, then the influence of quality and brand using PLS30 is concluded to have a significant influence on purchasing decisions of 81.2%.